2021
DOI: 10.13057/biodiv/d220258
|View full text |Cite
|
Sign up to set email alerts
|

Differential hierarchical metabolites expression of red/white Salacca sumatrana arillus and its molecular docking studies

Abstract: Abstract. Fendiyanto MH, Satrio RD, Widana IDKK, Pratami MP, Nikmah IA, Darmadi D. 2021. Differential hierarchical metabolites expression of red/white Salacca sumatrana Arillus and its molecular docking studies. Biodiversitas 22: 1014-1024. Salak Sidempuan (Salacca sumatrana) is one of the medicinal plants originating from tropical countries. However, there is very little research on the study of finding bioactive compounds in S. sumatrana using the metabolomic approach. Here, we use two population types of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Each microalga has a different amount of lipid content (Gunawan, 2010;Pratami et al, 2022). In other organisms, for example in snake fruit, lipid metabolites are relatively diverse (Fendiyanto et al, 2020;Fendiyanto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Each microalga has a different amount of lipid content (Gunawan, 2010;Pratami et al, 2022). In other organisms, for example in snake fruit, lipid metabolites are relatively diverse (Fendiyanto et al, 2020;Fendiyanto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the invasive alien species (IAS) C. hirta was identified based on morphological studies including flower and leaf structures. However, the potency of C. hirta extract nowadays is necessary to test the antibacterial, antibiotic, antifungal activity among several microorganisms (Schunack 1990;Bauer et al 1996;Andria 2000;Prayitno 2007), i.e., between plant extract-virus interaction (Fendiyanto et al 2021) and spoilage fungi -A. niger bioactivity , and fungal metabolites (Tabasso 2006). Plants from the Melastomataceae family have been studied extensively for their antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…6): 3363-3369, June 2021 3368 Phytochemical analysis revealed that C. hirta contains flavonoid, saponin, triterpenoid, and steroid compounds that showed antibacterial activity. Some secondary metabolites can influence the species growth and development, i.e., in the plant, arillus formation particularly in S. sumatrana is influenced by pyruvate and sulfur metabolism Fendiyanto et al 2021). Moreover, genes also influence the metabolism of some organisms, i.e., SnpB11 and OsGERLP influence the metabolism during species to avoid aluminum stress (Fendiyanto et al 2019a;Fendiyanto et al 2019b;Miftahudin et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultra-high-density consensus genetic map constructed in this study could be used to facilitate QTL mapping to discover novel genes controlling valuable traits. The traits can be observed in agronomy (Satrio et al 2021), morphology (Fendiyanto et al 2019a;Miftahudin et al 2021a), physiology (Fendiyanto et al 2019b), metabolites (Fendiyanto et al 2020(Fendiyanto et al , 2021b, or transcriptional level (Satrio et al 2019;Fendiyanto et al 2021a;Ratnadewi et al 2021). Published QTL map from any previous study could be integrated with the consensus genetic linkage map constructed in this study as the meta-QTL analysis.…”
Section: Consensus Genetic Map Of Sorghum Bicolormentioning
confidence: 93%